Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan Tradisional di Kabupaten Bone, Sulawesi Selatan - A Akhmad; A Amir; N Nurhapsa (JURNAL GALUNG TROPIKA, 2020)
Traditional fishers play an essential role in Indonesia's fishing business because most fishers are small-scale fishermen who are commonly referred to as conventional fishermen. This study's aim was to determine the factors that affect the income of traditional fishers in Bone Regency. The data used were cross-section data of 30 traditional fishermen in Tanete Riattang Timur and Sibulue Districts, Bone regencies. Data were analyzed by multiple linear regression analysis. The results showed that the variable price, amount of catch, and experience in fishing had a positive and significant effect on increasing fishermen's income in Bone Regency. Meanwhile, the variables of capital, number of workers, level of education, and number of dependents had no significant effect on fishermen's opinion. So the stability of fish prices during the fishing season needs attention from the government to increase fishermen's income.